“SIPODEH” Instant Red Ginger to Trigger Student Entrepreneurial Spirit - S. Syamsurizal; Sa’diatul Fuadiyah; Elsa Badriyya (Fakultas MIPA Universitas Negeri Padang, 2021)
West Sumatra is one of the largest ginger (Zingiber Officinale Rosc) producing provinces in Indonesia. The amount of ginger production in West Sumatra is increasing from year to year. In 2018 the total production of ginger in West Sumatra was estimated at 3,177,549 tons and in 2019 it increased to 4,508,462 tons. Ginger is one of the spice plants in Indonesia which is quite popularly used as traditional medicine. Ginger has a distinctive spicy taste, so it is quite often used as a drink to warm the body (to reject the wind). Nowadays, apart from white ginger which is generally consumed by the public, it turns out that there is another type of ginger which has more properties and a stronger spicy taste, namely red ginger (Zingiber officinale). Red ginger is predicted to be able to inhibit the infection process of the SARS-CoV-2 virus in human host cells and is predicted to be a good oral drug drink. Sudanese people who regularly drink red ginger do not get the flu / COVID-19 and in people who show symptoms of being infected with the corona virus, the symptoms are felt to be mild and recover quickly. This is because red ginger has been shown to increase immunity, increase IgM levels and reduce circulation of pro-inflammatory cytokines. The Biology student association already has a KWU (entrepreneurial) unit. The KWU unit has been engaged in the sale of food products and stationery which did not receive income during the Covid-19 pandemic. To overcome health problems during the Covid-19 pandemic and the business of the KWU HMJ Biology unit which was not optimal, an instant red ginger production business was developed.